The role of perceived justice in buyer-supplier relationships in times of economic crisis. Issue 4 (October 2019) - Matopoulos, Aristides; Didonet, Simone; Tsanasidis, Vaios; Fearne, Andrew
Abstract: This paper explores the importance of perceived organisational justice in times of crises, when supplier commitment has the potential to offset the negative impact of external pressures on business performance. We draw data from a survey of 117 suppliers of a major Greek grocery retailer. The grocery retail sector in Greece suffered considerably during the peak of the financial crisis, in 2016, providing a unique opportunity to explore the role of fairness in buyer-supplier relationships in times of crisis. The paper makes a distinct contribution by exploring the role that POJ plays in mitigating the impact of a financial crisis on suppliers' performance, both operational and financial. Moreover, we explore the role of commitment as a mediator between POJ and performance, in the specific context of a financial crisis. Our findings indicate that organisational justice influences firm performance through commitment and that the financial crisis moderates the relationship. Highlights: In times of crisis suppliers who perceive themselves to be fairly treated by their customers will devote additional resources to the relationship. The commitment that comes from being fairly treated pays dividends in 'normal' trading environments. In strong buyer-supplier relationships the underlying processes of collaborative working are more important than the contractual distribution of benefits.